2022
DOI: 10.1002/agj2.21047
|View full text |Cite
|
Sign up to set email alerts
|

Association between unmanned aerial vehicle high‐throughput canopy phenotyping and soybean yield

Abstract: Identifying agronomic traits correlated to grain yield can be very useful for soybean [Glycine max (L.) Merr.] breeding, especially if these traits can be measured through unmanned aerial vehicle high-throughput phenotyping rather than through manual measurements. The objective of the present study was to assess the association between canopy coverage and soybean grain yield through different statistical methodologies. A panel with 97 soybean genotypes was evaluated in two field experiments conducted in Paraná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Casagrande et al [16] used a drone-mounted RGB camera to capture field images and calculated crown coverage for soybeans during the V3-R1 stage based on the ratio of green pixels for each experimental unit. The results showed that, as the soybean growth stage progressed, soybean yield was positively correlated with canopy photosynthesis, with a correlation of 0.76 at the V9-R1 stage.…”
Section: Application Of Crop Htp Technologymentioning
confidence: 99%
“…Casagrande et al [16] used a drone-mounted RGB camera to capture field images and calculated crown coverage for soybeans during the V3-R1 stage based on the ratio of green pixels for each experimental unit. The results showed that, as the soybean growth stage progressed, soybean yield was positively correlated with canopy photosynthesis, with a correlation of 0.76 at the V9-R1 stage.…”
Section: Application Of Crop Htp Technologymentioning
confidence: 99%
“…There was a significant positive correlation between panicle number and yield at the maturity stage, and it could be recognized and counted directly on a certain regional scale in most monocotyledons (Jun et al, 2021;Wanli et al, 2021). However, in many dicotyledons, researchers can predict yields using only a large number of other indicators or measure the yield by picking and laying out fruits at maturity (Casagrande et al, 2022) or by picking and spreading out fruits at maturity (Li et al, 2021;Xiaobin et al, 2022), which greatly increases labor costs and is not beneficial to the development of high-throughput phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In soybean breeding programs, traits related to aboveground biomass, which is crucial for defining the canopy structure, are key selection targets [34]. Previous studies have focused on developing HTP techniques to estimate traits such as DW, canopy coverage rate, canopy volume, and PH [15, 16, 35]. Despite this progress, a gap remains in the HTP techniques available for capturing the phenotype of specific traits that determine canopy structure, such as NN, NB, and the extent of spread.…”
Section: Introductionmentioning
confidence: 99%